Competitive Strategies of Private Islamic Higher Education in Sidoarjo: Strategi Kompetitif Pendidikan Tinggi Islam Swasta di Sidoarjo - Abidah, Avivatul; Astutik, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The growing competition among higher education institutions requires Islamic universities to develop strong competitive strategies. Specific Background: Private Islamic Religious Higher Education Institutions (PTKIS) in Sidoarjo represent a significant portion of Islamic universities in Indonesia, yet their competitive edge remains underexplored. Knowledge Gap: Previous studies have not sufficiently addressed how PTKIS transform their strengths into marketable advantages in alignment with both Marx’s commodification theory and Porter’s strategic management framework. Aims: This study aims to analyze and reveal the competitive advantages of PTKIS through differentiation, cost leadership, and focus strategies. Results: Findings show PTKIS A emphasizes differentiation, while PTKIS B prioritizes cost-focused strategies. Both institutions commodify their advantages through curriculum innovation, industry-based programs, partnerships, human resource development, technology adoption, marketing, and superior student services. Novelty: The research highlights how PTKIS commodify competitive advantages into tangible educational products and services, offering a unique insight into the intersection of Islamic education and market-oriented strategies. Implications: The study provides a practical reference for higher education institutions and policymakers to strengthen strategic positioning, attract students, and ensure institutional sustainability. Highlights: PTKIS apply distinct strategies: differentiation vs. cost leadership. Competitive advantages commodified into curriculum, partnerships, and services. Offers practical insights for sustaining Islamic higher education competitiveness. Keywords: Competitive Advantages, Commodification, Islamic Universities, Strategic Management, Higher Education